2020
DOI: 10.1103/physreva.101.043619
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit-coupled bosons interacting in a two-dimensional harmonic trap

Abstract: A system of bosons in a two-dimensional harmonic trap with the presence of Rashba-type spinorbit coupling is investigated. An analytic treatment of the ground state of a single atom in the weak-coupling regime is presented and used as a basis for a perturbation theory in the interacting two-boson system. The numerical diagonalization of both the single-particle and the two-boson Hamiltonian matrices allows us to go beyond those approximations and obtain not only the ground state, but also the low-energy spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The solid lines correspond to profiles obtained with corrected direct diagonalization calculations with 20 single-particle modes, whereas the black dash-dotted lines are exact results given by Eq. (19). The inset shows a correlation parameter Sρ between the exact profiles (19) and the profiles obtained with the truncated diagonalizations (squares with dotted lines) and the corrected ones (circles with solid lines) as a function of the number of single-particle modes M .…”
Section: Results For Two Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid lines correspond to profiles obtained with corrected direct diagonalization calculations with 20 single-particle modes, whereas the black dash-dotted lines are exact results given by Eq. (19). The inset shows a correlation parameter Sρ between the exact profiles (19) and the profiles obtained with the truncated diagonalizations (squares with dotted lines) and the corrected ones (circles with solid lines) as a function of the number of single-particle modes M .…”
Section: Results For Two Particlesmentioning
confidence: 99%
“…(19). The inset shows a correlation parameter Sρ between the exact profiles (19) and the profiles obtained with the truncated diagonalizations (squares with dotted lines) and the corrected ones (circles with solid lines) as a function of the number of single-particle modes M .…”
Section: Results For Two Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…( 19). The inset shows a correlation parameter Sρ between the exact profiles (19) and the profiles obtained with the truncated diagonalizations (crosses with dashed lines) and the corrected ones (circles with solid lines) as a function of the number of single-particle modes M . ization calculation for g → +∞, the resulting energy is greater than the Tonks solution for infinite repulsion [14].…”
Section: Results For Two Particlesmentioning
confidence: 99%
“…While solving large many-body systems with approaches beyond mean-field is a very difficult task and only possible in special cases [12][13][14], few-particle systems can actually be amenable to exact treatments across the whole range of interactions and correlation strengths [15][16][17][18][19]. Several treatments of SOC in such systems have already been carried out [20][21][22][23][24][25][26] and, for example, a mapping to an effective spin model was recently suggested by a perturbative approach to account for weak Raman coupling [21]. It was also shown that, while there is no entanglement in the mean-field regime, in two-particle systems the ground state can be maximally entangled in the pseudo-spin space [23].…”
Section: Introductionmentioning
confidence: 99%